Managing athletes on the edge: Overtraining and the complexitites of coach's decision making - Smith, T.; Pope, C.; Penney, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In many elite sport performance contexts it is acknowledged that overtraining is a critical issue for coaches to understand, be able to recognise and respond to. While much scientific research has been conducted on overtraining, no diagnostic test exists that reliably predicts impending overtraining. The research reported in this study anticipated that successful endurance coaches have developed effective strategies for managing overtraining amongst elite athletes. In a first of its type, this study explored in depth the practices and beliefs of three highly successful professional elite rowing coaches as they managed the risk of athlete overtraining during crucial periods of intensive training. Methods: The coaches took part in a series of open-ended semi-formal interviews that explored their practices, philosophies and experiences. This study draws on sociological perspectives pertinent to coaching pedagogy and more specifically, the tenets of naturalistic decision making in exploring how the coaches define and make decisions about overtraining. This framework reflects recognition that coaching involves decision-making in complex and demanding situations. Results: The coaches were found to monitor the fatigue of their rowers through observation, communication and measures of training pace. In general, the intuitions and cues for overtraining employed by them had little in common with those promoted in the sport science and medical literature. Discussion: We contend that the coaches` decision-making is based largely on subjective processes and influenced by various stressors unique to their positions, which may explain the differences between their definitions and practices and those of the sport science and medical fraternity. We suggest that successful coaches have unique insights into this topical area that is worthy of further exploration.